1982
DOI: 10.1093/bja/54.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physostigmine on Morphine-Induced Postoperative Pain and Somnolence

Abstract: The effects of physostigmine 1 mg i.v. were studied on the analgesia, sedation and reduction in respiratory rate induced by morphine 10 mg/60 kg i.v. in 10 patients recovering from surgery. Within 5-10 min, physostigmine abolished the somnolent effect of morphine and restored the respiratory rate to pre-drug values. Analgesia, assessed by an independent observer and by the patient was, if anything, increased by physostigmine. The analeptic effect of physostigmine lasted 40-60 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 10 publications
1
22
0
2
Order By: Relevance
“…Nemirovsky et al (1985,1988,1990), Yaksh et al (1985,1995), Gillberg et al (1986, 1989, 1990 1991), Gordh et al (1989) also reported antinociceptive effect of cholinomimetics and anticholinesterases in the experimental animal models. [16][17][18][19][20][21][22][23][24] The results of the present study indicated that …”
Section: Discussionsupporting
confidence: 55%
“…Nemirovsky et al (1985,1988,1990), Yaksh et al (1985,1995), Gillberg et al (1986, 1989, 1990 1991), Gordh et al (1989) also reported antinociceptive effect of cholinomimetics and anticholinesterases in the experimental animal models. [16][17][18][19][20][21][22][23][24] The results of the present study indicated that …”
Section: Discussionsupporting
confidence: 55%
“…In the previous studies, some drugs and substances have been indicated as candidate antagonists for opiate-induced respiratory depression (Weinstock et al, 1980;1981;1982;Snir-Mor et al 1983;Willette et al, 1986;Elmalem et al, 1991;Berkenbosch et al, 1994;Ballanyi et al, 1997;Owen et al, 2000;Manzke et al, 2003;Lalley, 2004;. Among these candidates, physostigmine is the only clinically used drug that can pass the blood brain barrier, it is rapidly metabolized to eseroline and two other metabolites (Giacobini et al, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous articles have proposed various candidates as antagonistic drugs for opiate-induced respiratory depression (Weinstock et al, 1980;Weinstock et al, 1981;Weinstock et al, 1982;Snir-Mor et al 1983;Willette et al, 1987;Elmalem et al, 1991;Berkenbosch et al, 1994;Ballanyi et al, 1997;Owen et al, 2000;Manzke et al, 2003;Lalley, 2004;. However, none of these have been applied to clinical practice thus far because most are experimental chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…2~ Physostigmine has also reversed postoperative morphine-induced respiratory depression, without impairing analgesia, probably due to physostigmine's anticholinergic action in the medulla. 21 However, physostigmine did not alter morphine-induced respiratory depression in unpremedicated volunteers. 19 Excitatory CNS phenomena following general anaesthesia have been documented previously.…”
Section: Discussionmentioning
confidence: 92%